Penerapan Media Pembelajaran Pop Up Book Di Masa Belajar Dari Rumah - Echa Surya Kunanti (Program Studi PGSD Kampus UPI di Serang, 2020)
During the pandemic, students are required to learn from home in an effort to prevent the spread of the covid-19 virus. As educators, teachers must ensure teaching and learning activities continue, even though students are at home. Teachers are required to design learning innovations by utilizing online media so that learning is carried out online. Online learning is carried out via a computer or laptop that is connected to an internet network connection or by using an Android cellphone. However, many schools in some areas are unable to conduct online learning due to several factors. So the school carries out offline learning or learning outside the network so that it continues to carry out learning activities. Learning from home is certainly not as effective as learning in the classroom, therefore, as a teacher, you must create meaningful learning by using learning media as attractive as possible so that learning objectives can be achieved. As an effort to improve social studies learning outcomes for fifth grade elementary school students, namely the use of pop up book learning media. In this research, the method used is a qualitative method with a descriptive approach. The research was conducted at SD Negeri 010231 Aras. With a sample of 27 students in class V. The results of this study, an increase in student social studies learning outcomes by using pop up book learning media.